Model Pembelajaran Flipped Classroom Berbasis Language Activity: Studi Evaluatif Pembelajaran Maharah Kalam - Akhirudin, Akhirudin; Rahman, Rifqi Aulia; Annas, Azwar; Syakir Hidayat, Ahmad Fadhel (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2024)
This study explores the implementation and evaluation of the Flipped Classroom Model in Arabic language learning, specifically focusing on Maharatul kalam (speaking skills) at MAN 2 Wonosobo post-COVID-19 pandemic. The Flipped Classroom Model, a 21st-century learning approach, flips in-class and out-of-class activities, allowing students to engage with learning materials independently before face-to-face sessions. Through qualitative evaluative methods, including case study design, data were collected from stakeholders including policymakers, teachers, and students. Analysis involved SWOT analysis to identify strengths, weaknesses, opportunities, and threats. Results indicate significant improvements in students' analytical skills, highlighting the model's effectiveness. However, challenges such as technological dependency and uneven student participation were noted. Despite these, opportunities for personalized learning and access to global educational resources were recognized. Overall, the study underscores the relevance and potential of the Flipped Classroom Model in enhancing Arabic language learning post-pandemic, while emphasizing the need for ongoing monitoring and adaptation